Perkembangan Hukum Ekonomi Indonesia Melalui Cyber Notaris - Hayun, Hayun; Mashendra, Mashendra; Hasri, Hasirudin; Aulia, Riska (Legal Standing : Jurnal Ilmu Hukum, 2025)
This research aims to analyze the development of Indonesian economic law through the implementation of the cyber notary system. The method used is a normative approach. The data used are legal materials, both primary (legislation), secondary (doctrine, jurisprudence), and tertiary (dictionary, legal encyclopedia), to analyze and interpret legal norms. Data sources include laws and regulations, jurisprudence (court decisions), legal doctrine (opinions of legal experts), and other legal materials such as draft laws and minutes of discussion. The results show that cyber notarization increases the value of electronic documents by legalizing them, for example, in addition to digitizing notary operations. Nevertheless, the implementation of this project will take a considerable amount of time due to the many components that must be prepared. It is stipulated in Article 1868 of the Indonesian Civil Code that an authentic deed is a legal document made before a public official and in a certain form stipulated by law.